Lions painting, Chauvet Cave (museum replica) - HTO (Wikimedia Commons, 2009)
Notice iconographique issue de Wikimedia Commons. Titre: Lions painting, Chauvet Cave (museum replica). Lions painted in the Chauvet Cave (Ardèche, France). This is a replica of the painting from the BrNo museum Anthropos (Czech Republic). The absence of the mane sometimes leads to these paintings being described as portraits of lionesses.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; Wikimedia Commons